THE FOUNDATION OF BALUMBUNG MUSEUM SITUBONDO EMPOWERMENT TO REALIZE CULTURAL HERITAGE CONSERVATION BASED ON COMMUNITY PARTICIPATION - Sumarjono Sumarjono; Kayan Swastika; A. Ryan Pratama (UPT Penerbitan Universitas Jember, 2022)
The Community in this Partnership Service Program is the Museum BalumbungSitubondo Foundation (YMBS), which is a cultural heritage preservation organization based in Situbondo. Three main problems to solve this community problems is the lack of knowledge of YMBS human resources regarding: 1) megalithic cultural heritage; 2) mastery of IT and online publications; 3) museum curatorial. The approach method used is in the form of community empowerment. Operationally, the community empowerment approach method is realized in the form of activities: 1) megalithic cultural dialogue; 2) field practice assistance to megalithic sites in Situbondo; 3) IT-based cultural heritage publication training; 4) video creation assistance; 5) museum curatorial training; and 6) museum curatorial practice assistance. Its external achievements are: 1) Balumbung Museum Collection Catalog which can be accessed online; 2) Description of the Balumbung Museum Collection; 3) Videos About Balumbung Museum Collection.Keywords: Empowerment, BalumbungCommunity, Heritage, Situbondo